THE ROLE OF READING IN PROMOTION LIFELONG LEARNING AND INTELLECTUAL GROWTH - Xo’jayeva Xayriniso; Abdurahmonov T (TADQIQOTLAR.UZ, 2024)
Abstract: Reading plays a pivotal role in promoting lifelong learning and intellectual growth, offering individuals the tools to continuously expand their knowledge, enhance cognitive abilities, and engage with the world around them. Through regular reading, individuals can develop critical thinking, analytical skills, and a broader vocabulary, all of which contribute to their intellectual and professional development. Reading also fosters empathy, creativity, and emotional intelligence by exposing readers to diverse perspectives and experiences. Furthermore, it stimulates mental health by reducing stress and supporting cognitive longevity. By cultivating a growth mindset, reading encourages individuals to embrace learning as an ongoing process, making it a foundational activity for lifelong personal and intellectual growth. This article highlights the multifaceted ways in which reading contributes to the development of a well-rounded, informed, and adaptable individual.